COMP (Cartilage Oligomeric Matrix Protein), a Novel PIEZO1 Regulator That Controls Blood Pressure. Issue 3 (March 2022) - Wang, Hui; Yuan, Ze; Wang, Bianbian; Li, Bochuan; Lv, Huizhen; He, Jinlong; Huang, Yaqian; Cui, Zhen; Ma, Qiannan; Li, Ting; Fu, Yi; Tan, Xiaoli; et al.
Abstract : Background: Vascular endothelial cells are critical for maintaining blood pressure (BP) by releasing biologically active molecules, such as nitric oxide. A non-endothelial cell resident matricellular protein, COMP (cartilage oligomeric matrix protein), plays a pivotal role in maintaining cardiovascular homeostasis, but little is known about its regulatory effect on BP. Methods: Mice were infused with AngII (angiotensin II; 450 ng/kg per minute) for 3 days via an osmotic minipump, and BP was monitored by a tail-cuff system. Second-order mesenteric arteries were isolated from mice for microvascular tension measurement. Nitric oxide was detected by an electron paramagnetic resonance technique. Small-interfering RNA transfection, co-immunoprecipitation, bioluminescence resonance energy transfer assays, and patch-clamp electrophysiology experiments were used for further detailed mechanism investigation. Results: COMP −/− mice displayed elevated BP and impaired acetylcholine-induced endothelium-dependent relaxation compared with wild-type mice with or without AngII. Inhibition of eNOS (endothelial nitric oxide synthase) abolished the difference in endothelium-dependent relaxation between wild-type and COMP −/− mice. Furthermore, COMP directly interacted with the C-terminus of Piezo1 via its C-terminus and activated the endogenous Piezo1 currents, which induced intracellular Ca 2+ influx, Ca 2+ /calmodulin-dependent protein kinase type II and eNOS activation, and nitric oxide production. The Piezo1 activator, Yoda1, reduced the difference in endothelium-dependent relaxation and BP in wild-type and COMP − /− mice. Moreover, COMP overexpression increased eNOS activation and improved endothelium-dependent relaxation and BP. Conclusions: Our study demonstrated that COMP is a novel Piezo1 regulator that plays a protective role in BP regulation by increasing cellular Ca 2+ influx, eNOS activity, and nitric oxide production. Abstract : Supplemental Digital Content is available in the text.